INFLUENCE OF BIRTH WEIGHT ON STRUCTURAL AND GEOMETRIC PARAMETERS OF THE MYOCARDIA IN ADOLESCENTS WITH EXCESSIVE FAT DEPOSIT - Миняйлова, Наталья Николаевна; Ровда, Юрий Иванович; Ведерникова, Алена Владимировна; Маталасова, Мария Сергеевна; Хоботкова, Татьяна Сергеевна (Mother and Baby in Kuzbass, 2022)
The World Health Organization has now recognized the predictive value of birth weight (BW). The association of low birth weight with the development of cardiovascular disease is one of the priorities. Over the past two decades, there has been increased interest in the potential health risks associated with high (> 4000 g) BW at birth.The relative frequency (P [95% CI]) of those born with low (< 2500 g) and large (> 4000 g) BW among 285 adolescents with a body mass index over the 85th percentile was 14.7 [7.9; 21.7] % and 21.05 [13.3; 28.9] %, respectively, which is 2.5 and 3.5 times higher than the population level in Russia. In a sample of 126 overweight adolescents aged 12-16 years, a linear relationship was found between the actual LVMM (g) and BW at birth (rs = 0.37; p = 0.014).Comparative analysis of echocardiography parameters, including the mass and mass index of the left ventricular myocardium (LVMM and LVMMI) showed that in the examined born with a BW of less than 2500 g, relative to those born with a BW of 3100-3800 g, the following structural and geometric parameters of the myocardium were statistically significantly lower: end-diastolic size and volume of the left ventricle, stroke volume, ejection fraction, LVMM and LVMMI, and above – the relative wall thickness of the left ventricle. In those born with a large weight, relative to the group of adolescents with an average birth weight, on the contrary, the following were statistically significantly higher: the size of the left atrium, the final systolic and diastolic dimensions and the volume of the left ventricle, as well as the stroke volume, and the maximum LVMM was determined.In the general group of 126 subjects with MT at birth, the following correlated positively: the end systolic and diastolic volumes of the left ventricle, its end diastolic size, stroke volume and LVMM, and negatively – the relative wall thickness of the left ventricle. At the same time, only in the group of those born with low birth weight in the pubertal period, LVMMI directly correlated with BW at birth (r = 0.33; p = 0.01), in the other groups no significant association was obtained.
Keywords: body weight at birth; structural and geometric parameters of the myocardium; excessive fat deposition; adolescents; cardioremodeling